Self‐obtained vaginal swabs are not inferior to provider‐performed endocervical sampling for emergency department diagnosis of Neisseria gonorrhoeae and Chlamydia trachomatis. (24th March 2021) - Chinnock, Brian; Yore, Mackensie; Mason, Jessica; Kremer, Mallory; Farshidpour, Leyla; Lopez, Diana; Castaneda, Jannet
Abstract: Objective: Provider‐performed endocervical sampling (PPES) in the diagnosis of Neisseria gonorrhoeae (NG) and Chlamydia trachomatis (CT) may be difficult to perform in a busy emergency department (ED) due to patient preference, availability of the pelvic examination room, or provider availability. Our objective was to assess if self‐obtained vaginal swabs (SOVS) were noninferior to PPES in the ED diagnosis of NG/CT using a rapid nucleic acid amplification test (NAAT). Methods: We conducted a prospective observational cohort study in a single ED. Participants were adult female English‐ and Spanish‐speaking patients in whom the ED provider felt that NG/CT testing was warranted. Each patient had SOVS and PPES performed. For SOVS, a research associate reviewed a one‐page handout describing the procedure but gave no other assistance. Patients answered survey questions regarding acceptability of SOVS and symptomatology. We established a minimum sensitivity of 90% for SOVS to be considered clinically noninferior to standard PPES. Results: A total of 533 patients completed enrollment and answered survey questions, 515 of whom had laboratory results for both SOVS and PPES. There were 86 patients with a positive result: 29 with NG, 47 with CT, and 10 with coinfection. SOVS had a sensitivity of 95% (95% confidence interval = 88% to 99%) for the detection of NG/CT when compared to PPES. SOVS were felt to be an acceptable collection method in 93% of patients and 75% preferred SOVS to PPES. Conclusion: SOVS are noninferior to PPES in NG/CT diagnosis using a rapid NAAT in ED patients and surveys indicate high patient acceptability.